Pemberdayaan Masyarakat Desa Bendolo melalui Diversifikasi Olahan Talas (Colocasia esculenta) - Sutrisno Adi Prayitno; Heri Purnama Pribadi; Dinta Sugiarto; Ainanda Alfatina (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Bendolo Village is one of the villages located in Sawahan District, Nganjuk Regency. Many of the people of Bendolo Village cultivate taro plants, but the yields are not used optimally. The crops are only sold raw at low prices due to limitations in processing or utilization. Ignorance of taro processing technology makes taro plants just planted and not a priority in processing. The crops are only sold fresh. People rarely process it in the form of food or snacks. Hence, community service activities (PKM) aim to increase the knowledge and income of the family welfare empowerment group (PKK) by utilizing the diversification of processed taro into taro noodles and taro chips. Implementing the community service uses lectures, discussions, and direct demonstrations related to taro processed products. The activities began with a demonstration of raw material handling, how to use the noodle grinder and mixing materials to packaging and storage. The result of the training is that almost 100% of the family welfare empowerment group (partners) can make taro processed and pack it well.